THE INFLUENCE ANALYSIS OF HUMAN RESOURCES, CAPITAL INCOME, DEVELOPMENT EXPENDITURE BUDGET AND REAL GRDP ON HUMAN DEVELOPMENT INDEX IN MANDAILING NATAL REGENCY - Hamonangan Nasution; Eko Wahyu Nugrahadi (Universitas Negeri Medan, 2020)
Quality of Human Resources in developing countries and poor countries is a very serious issue to be addressed . When the quality of human resources do not keep pace with the progress of time involved will lead to underdevelopment , poverty and unemployment which in turn trigger the overflow gap , inequality and adversity . This study aims to look at and determine how much influence Number of Qualified Persons , Budget Development, Real Gross Domestic Product and Shopping Structural Transformation of the Human Development Index in Mandailing Natal Regency . Used in measuring and analyzing time series data ( time series ) in the form of quarters in the period 2003 : Q1 - 2012 : Q4 . Data analysis using OLS ( Ordinary Least Square ) which is multiple regression . The results showed RHQ variable positive and significant effect on the HDI Mandailing Natal district , ABP variablespositive and significant effect on the HDI Mandailing Natal Regency ,any one significant negative effect on the HDI in Mandailing Natal Regency is Shopping Structural Transformation , while variable GRDPCP positive and significant impact on HDI of Mandailing Natal Regency. in α = 5%. The result of the regression model of HDI policy is R-squered=0,8967 whereas the presence of the model is R-squered BTS= 0,8907 in Mandailing Natal Regency, after the classic test. This means that in thebase stations are very well organized affect HDI, whereas if done deviation will adversely affect the HDI.